Transcriptomic signatures in response to antioxidants supplementation in Korean cattle beef, Hanwoo: a 7-month feeding study - Lee, Kangwook; Choi, La Yoon; Ahn, Jun Sang; Song, Jae Yong; Park, Joong Kook; Yun, Suk Jun; Lee, Jeong Heon; Shin, Eui-Cheol; Yeom, Soo-Jin; Zhao, Jiangchao; Cho, Tae Jin; Oh, Nam Su; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe present study investigated the effects of antioxidant supplementation on the transcriptomic profiles of Hanwoo cattle during a 7-month feeding trial.MethodsTwelve castrated Hanwoo cattle were randomly assigned to two groups: a control group (CON) and a group supplemented with antioxidants (FEED), consisting of vitamin C, vitamin E, and selenium. Growth performance and carcass traits were evaluated, and liver transcriptomic changes were assessed using RNA sequencing.Results and discussionWhile no significant differences were observed in phenotypic traits such as weight gain and feed conversion ratio, transcriptomic analysis identified 641 differentially expressed genes between the CON and FEED groups. Functional enrichment analysis revealed that differentially expressed genes were mainly associated with transcription regulation, pseudouridine synthesis, and mitochondrial function. These findings suggest that antioxidant supplementation elicits significant molecular changes in the liver, particularly affecting transcriptional activity and mitochondrial processes, even in the absence of detectable phenotypic differences.